Becoming futile: the emotional pain of treating COVID-19 patients - Rodriquez, Jason (Frontiers in Sociology, 2023)
Introduction The COVID-19 pandemic has had a profoundly detrimental impact on the emotional wellbeing of health care workers. Numerous studies have shown that their rates of the various forms of work-related distress, which were already high before the pandemic, have worsened as the demands on health care workers intensified. Yet much less is known about the specific social processes that have generated these outcomes. This study adds to our collective knowledge by focusing on how one specific social process, the act of treating critically ill COVID-19 patients, contributed to emotional pain among health care workers. Methods This article draws from 40 interviews conducted with intensive care unit (ICU) staff in units that were overwhelmed with COVID-19 patients. The study participants were recruited from two suburban community hospitals in Massachusetts and the interviews were conducted between January and May 2021. Results The results show that the uncertainty over how to treat critically ill COVID-19 patients, given the absence of standard protocols combined with ineffective treatments that led to an unprecedented number of deaths caused significant emotional pain, characterized by a visceral, embodied experience that signaled moral distress, emotional exhaustion, depersonalization, and burnout. Furthermore, ICU workers’ occupational identities were undermined as they confronted the limits of their own abilities and the limits of medicine more generally. Discussion The inability to save incurable COVID-19 patients while giving maximal care to such individuals caused health care workers in the ICU an immense amount of emotional pain, contributing to our understanding of the social processes that generated the well-documented increase in moral distress and related measures of work-related psychological distress. While recent studies of emotional socialization among health care workers have portrayed clinical empathy as a performed interactional strategy, the results here show empathy to be more than dramaturgical and, in this context, entailed considerable risk to workers’ emotional wellbeing.